Bar Code Detection Using Omnidirectional Vision for Automated Guided Vehicle Navigation - Zahari, Taha; Jessnor Arif, Mat Jizat; Ismayuzri, Ishak (2012)
In this paper, a study on detectability and readability of barcodes using omnidirectional vision system for automated guided vehicle is presented. Images from omnidirectional camera are known to be distorted against the height of the object. We present an algorithm for detecting and reading barcodes successfully without correcting the image distortion. Experiments were conducted both when the AGV was in motion and at rest. Three contributing factors were identified for successful barcodes detection and reading.